1975
DOI: 10.1007/bf01380047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the jamming avoidance responses in Gymnotoid and Gymnarchid electric fish: A case of convergent evolution of behavior and its sensory basis

Abstract: Summary. 1. A behavioral response conforming to defining features of the jamming avoidance response (JAR) previously reported in Eigenmannia and Apteronotus of the Cypriniformes is found in Gymnarehus of the Mormyriformes.2. Other parallel specializations of these groups are noted, of which the most relevant is the character of the electric organ discharge (EOD); it is quasisinnsoidal, high in repetition rate and highly regular in each of the genera. The same features are found in Sternopygus but it lacks a JA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 26 publications
(20 reference statements)
2
64
0
Order By: Relevance
“…EOD jitter measured in this study confirms the measurement of EOD jitter by Bullock et al (1975). The frequency "singing" described in Bullock et al (1975), however, was not observed, and all individuals showed stable EOD in a given measurement period (10 sec).…”
Section: Stability Of Eodssupporting
confidence: 84%
See 3 more Smart Citations
“…EOD jitter measured in this study confirms the measurement of EOD jitter by Bullock et al (1975). The frequency "singing" described in Bullock et al (1975), however, was not observed, and all individuals showed stable EOD in a given measurement period (10 sec).…”
Section: Stability Of Eodssupporting
confidence: 84%
“…The behavioral sensitivity to microsecond time disparities is not unique to Gymnarchus; similar or even better temporal sensitivity has been shown in the electrosensory system of a gymnotiform electric fish as well as other vertebrate auditory systems (Rabizza and Masterton, 1972;Brown et al, 1978;Knudsen et al, 1979;Simmons et al, 1983). Despite independent evolution of the electrosensory and electrogeneric systems (Lauder and Liem, 1983), gymnotiform electric fish Eigenmannia performs JARs that are very similar to those of Gymnarchus (Bullock et al, 1975) using identical computational algorithms, consisting of multiple steps of amplitude and phase processing (Bullock et al, 1975;Heiligenberg et al, 1978;Heiligenberg and Bastian, 1980b;Heiligenberg, 1991;Kawasaki, 1993aKawasaki, , 1996. Eigenmannia exhibits comparable phase sensitivity to that found in this study (Rose and Heiligenberg, 1985b;Carr et al, 1986a).…”
Section: Temporal Sensitivity Expressed In the Jarmentioning
confidence: 82%
See 2 more Smart Citations
“…One of the fish usually shows a so-called jamming avoidance behavior and changes its EOD frequency to improve object localization (Bullock et al, 1975;Bullock et al, 1972;Watanabe and Takeda, 1963). This example illustrates a completely different aspect of behavioral modulation of sensory processing because sensory information is actively changed before even reaching the receptors.…”
Section: Examples From Various Modalitiesmentioning
confidence: 99%